Vulnerability Mapping of Dengue Hemorrhagic Fever (DHF) Cases in West Java Province in 2023 - Arifanissa Maramis; Bambang Wispriyono (Indonesian Journal of Global Health Research, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the public health problems that needs serious attention, because this disease contributes a high mortality rate. Dengue disease related to environmental conditions, climate, population density, and community behavior. West Java is the highest province of dengue cases in Indonesia in 2023 that has 19,328 cases with the number of deaths due to dengue reaching 134 people. This study aims to map the spread of the disease by describing the distribution of dengue cases and describing the level of vulnerability through risk factors from dengue. The method used in this study is descriptive research with a Geographic Information System (GIS) approach. The data used is secondary data from the official website of the Central Statistics Agency (BPS) of West Java Province. Data analysis was carried out using QuantumGIS (QGIS) version 3.40.4 which is open-source software. The scoring results of 27 districts and cities in West Java Province show that the priority areas in handling of dengue cases are Bogor City, Bekasi City, and Bogor Regency which are the areas with the highest level of vulnerability. This study is expected to provide an overview of the distribution of cases and the level of dengue vulnerability based on districts/cities in West Java Province, so that studies can be carried out on dengue disease prevention and control programs, especially in areas with the highest level of vulnerability.